A new track reconstruction algorithm for the Mu3e experiment based on a fast multiple scattering fit - Kozlinskiy, Alexandr; Schöning, André; Kiehn, Moritz; Berger, Niklaus; Schenk, Sebastian (Journal of Instrumentation, 2014)
A new fast track reconstruction algorithm developed for the high track multiplicity environment of the Mu3e experiment where track uncertainties are dominated by multiple scattering is presented. The goal of the Mu3e experiment is to search for the LFV decay μ+ → e+e−e+. To reach the sensitivity of 10-16 the experiment will be performed at a future high intensity beam line (HiMB) at the Paul-Scherrer Institute (Switzerland) providing more than 109 muons per second. Muons with a momentum of about 28 MeV/c are stopped on a target. Their decay at rest, in which mainly low momentum electrons with energies below 53 MeV are produced, is measured by the Mu3e tracking detector consisting of four cylindrical layers of thin silicon pixel sensors. The high granularity of the pixel detector with a pixel size of 80 × 80 μm2 allows for precise track reconstruction in the high occupancy environment of the Mu3e experiment reaching up to 100 tracks per readout frame of 50 ns. These tracks will be reconstructed online using a trigger-less readout scheme. The implementation of a fast 3-dimensional multiple scattering fit based on hit triplets, where spatial uncertainties are ignored, is described and performance results in the context of Mu3e experiment are presented. Also the implementation on Graphics Processor Units (GPUs) for fast online reconstruction is discussed.